"Decoupled" Farm Program Payments are Really Decoupled: The Theory. (22nd June 2016) - Chambers, Robert G.; Voica, Daniel C.
Abstract: Lump‐sum transfers to farmers are commonly believed to affect the production choices of farmers in the presence of risk and uncertainty. This paper shows that if farmers have off‐farm investment and employment opportunities, production decisions are decoupled from lump‐sum subsidies in the presence of risk and uncertainty. Our results are reconciled with existing results by showing that previously identified production adjustments are portfolio adjustments.